2021
DOI: 10.1166/jbt.2021.2551
|View full text |Cite
|
Sign up to set email alerts
|

Lepidium sativumand Its Biogenic Silver Nanoparticles Activate Immune Cells and Induce Apoptosis and Cell Cycle Arrest in HT-29 Colon Cancer Cells

Abstract: There is an increased demand for plants with antioxidants and anticancer properties. Lepidium sativum L. is an edible plant with medical importance. In this study, we aimed to investigate the anticancer activity; antioxidant capacity and antibacterial impact of Lepidium sativum L. seed acetone extract (LSSAExt), alone and with its biogenic silver nanoparticles (AgNPs). LSSAExt-produced AgNPs were characterized using SEM, XRD and Vis/UV analysis. Biomolecules in LSSAExt and LSSAExt + AgNPs were explored utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The seed extract of L. sativum alone and with silver nanoparticles showed significant anticancer activity against HT-29 colon cancer cell lines by inducing apoptosis and mitotic cell arrest. They also increase the p53 expression and prevent cell division of HT-29 colon cancer cells [ 90 ].…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The seed extract of L. sativum alone and with silver nanoparticles showed significant anticancer activity against HT-29 colon cancer cell lines by inducing apoptosis and mitotic cell arrest. They also increase the p53 expression and prevent cell division of HT-29 colon cancer cells [ 90 ].…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…L. sativum seed acetone extract and its combination with biogenic silver nanoparticles were found to be nontoxic to splenic cells [ 90 ].…”
Section: The Challenge Of Standardizing Extract Toxicity and Bioavailability Of The Extractmentioning
confidence: 99%
“…Liver function tests were conducted by evaluating the level of total protein and total bilirubin, serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT), and the kidney function was assessed by quantitating serum creatinine and urea using the method previously described ( Ibrahim et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…They also found that there was a synergistic effect on apoptosis when using cells expressing uracil phosphoribosyltransferase (UPRT) and non-UPRT-expressing cells in the presence of fluorouracil (5-FU). The researchers observed that AgNPs not only induced apoptosis but also sensitized cancer cells in these experimental conditions [219].…”
Section: Anticancer Activity Of Agnpsmentioning
confidence: 97%